CRITICAL STUDY OF EDUCATIONAL PHILOSOPHY ON THE PANCASILA STUDENT PROFILE IN THE ERA OF REVOLUTION 4.0 AND HUMAN SOCIETY 5.0 - Astuti, Ni Wayan Widi; Suastra, I Wayan (Indonesian Journal of Educational Development (IJED), 2024)
Indonesian needs a generation that needs to implement Pancasila values in their lives. Pancasila student profile is basically a name for the character of students in everyday life which is instilled based on school culture in the form of intra-curricular, extracurricular, and student profile character strengthening projects. Pancasila through work culture using literature study methods that refer to relevant previous studies or research. Literature study is a literature review which is a description of literature that is relevant to a particular field or topic. The design of this research is to collect literacy data source related to the Pancasila student profile. Then it will be explained using a comprehensive descriptive-analytical analysis method. This Pancasila Student Profile was created as a guide for Indonesian education. Not only is education policy at the national level, it is hoped that it will become a guide for educators in building children's character. Students who have this profile are students who have fully awakened the six dimensions that form it, namely Faith, devotion to God Almighty and noble character. Independent. Collaborative. Global diversity. Critical reasoning. Creative. This strategy is the Pancasila student profile with a project to strengthen the Pancasila student profile. Instilled in students in Indonesia starting from elementary school level to high school and/or vocational level. So that students can become complete 5.0 citizens who are able to face the demands of work in the industrial revolution 4.0 era when they finish school and enter society.